2006
DOI: 10.1681/asn.2005050549
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Pathway Blockade Slows Progression of Diabetic Kidney Disease in Rats

Abstract: Recent data suggest that the phosphatidylinositol 3-kinase (PI3-K)/Akt/mammalian target of rapamycin (mTOR) pathway is important in diabetic nephropathy. The effect of mTOR blockade by sirolimus (SRL) in diabetic kidney disease in rats was investigated. Diabetes was induced by streptozotocin in male Sprague-Dawley rats. Sixteen weeks later, diabetic animals were divided into the following groups: diabetes (D; n ‫؍‬ 8), diabetes ؉ SRL at 1 mg/kg per d, SRL trough level 2.3 ؎ 0.25 ng/ml (D؉SRL; n ‫؍‬ 7); and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
207
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(219 citation statements)
references
References 39 publications
8
207
1
3
Order By: Relevance
“…It is imaginable that VEGF might be needed for endothelial repair for a short period and later exert negative effects in terms of favoring glomerular hypertrophy and fibrotic mechanisms. However, the implication of the VEGF system in different models of disease such as the model of antiThy1.1 nephritis 23 or of diabetic nephropathy 20 or ours might be different and not sufficient to explain the distinct effects of mTOR-I treatment in these different models or in transplant patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is imaginable that VEGF might be needed for endothelial repair for a short period and later exert negative effects in terms of favoring glomerular hypertrophy and fibrotic mechanisms. However, the implication of the VEGF system in different models of disease such as the model of antiThy1.1 nephritis 23 or of diabetic nephropathy 20 or ours might be different and not sufficient to explain the distinct effects of mTOR-I treatment in these different models or in transplant patients.…”
Section: Discussionmentioning
confidence: 93%
“…We could further show that sirolimus treatment was accompanied by less interstitial inflammation and fibrosis, less tubular atrophy, and less glomerular lesions after 3 mo of treatment. In a rat model of type 1 diabetes with diabetic nephropathy, Lloberas et al 20 demonstrated the beneficial effects of sirolimus treatment. They showed that low-dosage treatment with trough concentrations of 2.3 ng/ml led to significantly decreased albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of mTOR inhibition have recently been reported in several rat models of chronic kidney disease, i.e., hypertensive 5 ⁄6 nephrectomy, diabetic nephropathy, hypertrophy following unilateral nephrectomy, tubulointerstitial fibrosis due to urethral obstruction or nephrotic syndrome, and polycystic kidney disease (2,5,10,19,26,29). These beneficial results are now expanded toward a progressive model of human mesangioproliferative nephropathy as a leading cause of end-stage kidney disease worldwide (13,14).…”
Section: Discussionmentioning
confidence: 98%
“…High glucose augments TGF-␤ mRNA in proximal tubular epithelial cells; successful translation of TGF-␤ mRNA into protein, however, depends on PDGF (105). Recently, Lloberas et al (106) reported that administration of rapamycin to rats with streptozotocininduced type 1 diabetes resulted in reduction in TGF-␤ mRNA expression, mesangial matrix expansion, and albuminuria but not glomerular hypertrophy.…”
Section: Diabetic Nephropathymentioning
confidence: 99%